residual-Based Tests for Cointegration in Models with Regime Shifts - Allan w. Gregory; Bruce E. Hansen (Queen's University, Department of Economics, 1992)
In this paper we examine tests for cointegration which allow for the possibility of regime shifts. We propose augmented Dickey-Fuller (ADF) and Phillips type tests designed to test the null of no cointegration against the alternative of cointegration in the presence of a possible regime shift. In particular we consider cases where the intercept and/or slope coefficients have a single break of unknown timing. A formal proof is provided for the limiting distributions of the various tests for the regime shift model (both a level and slope change). Critical values are calculated for the tests by simulation methods and a simple Monte Carlo experiment is conducted to evaluate finite sample performance. In the limited set of experiments, we find that the tests can detect cointegrating relations when there is a break in the intercept and/or slope coefficient. For these same experiments, the power of the conventional ADF test with no allowance for regime shifts falls sharply. As an illustration we test for structural breaks in the U.S. long-run money-demand equation using annual and quarterly data.
Keywords: C12; C15; C22; C25; 330; level shift; regime shift; cointegration; Brownian motion